An estimation of fluoride release from various dental restorative materials at different pH: In vitro study - R N Bahadure; R K Pandey; R Kumar; K Gopal; R K Singh (Wolters Kluwer Medknow Publications, 2012)
Background: In the mid of 1980s, the cariostatic effect of fluoride ions on enamel caries had been demonstrated in many studies. The use of fluoride releasing dental restorative materials has seen increasing from many years for the specific purpose of leaching of fluoride into the surrounding tissues to inhibit secondary dental caries as well as prevention of caries in the newly erupted tooth. In the dental caries, acidic environment causes the demineralization of tooth structure and also affect the restorative margins of dental restoration. Aim: various restorative materials show different behavior in different pH conditions of oral cavity. Thus, the aim of this study was to evaluate the fluoride release of the various restorative materials at different pH. Design: In this in vitro study, 30 samples of each dental restorative material were prepared and grouped into five with six samples in each group as per the pH of the solution 4.3, 4.6, 5.0, 5.5, and 6.2. All the samples were subjected to alternate cycling of the demineralizing solution (6 h) and remineralizing solution (18 h) for 15 days. Results: the fluoride release was measured by using fluoride ion specific electrode and digital ion analyzer. The result showed that the fluoride release rate was significantly higher in first day and reduced after third day to nearly constant level. At pH 4.3, the fluoride release was highest and lowest at pH 6.2. Conclusion: the Amalgomer CR showed the highest fluoride release among all the experimental dental restorative materials.